Application of The Principle of Notary Caution In Handling The Legalization of Rental Agreements Towards Mortgage Right Objects - Furqon, Muhammad Tanzilul; Jatmiko, Sri Wahyu (Dinasti Research, 2025)
In lease agreements, the contract is established in writing. Some collateral institutions require the use of a notarial deed. Even if not mandatory, the lease agreement can still be prepared by or executed before a notary. A collateral deed prepared by a notary, as required, will naturally specify the object of the agreement. However, lease agreements often involve legalization within the contract, which frequently leads to conflicts. The question arises regarding the notary’s liability when such issues occur. This research is a normative study, focusing on the notary’s liability in the legalization of lease agreements involving collateral objects under the principle of prudence. Kata Kunci : Agreement, Notary, Principle of Prudence